Development of a new polyspecific antivenom for snakebite envenoming in Sri Lanka: Analysis of its preclinical efficacy as compared to a currently available antivenom. (November 2016) - Villalta, Mauren; Sánchez, Andrés; Herrera, María; Vargas, Mariángela; Segura, Álvaro; Cerdas, Maykel; Estrada, Ricardo; Gawarammana, Indika; Keyler, Dan E.; McWhorter, Kimberly; Malleappah, Roy; Alape-Girón, Alberto; et al.
Abstract: A new whole IgG, freeze-dried, polyspecific antivenom was prepared from the plasma of horses immunized with the venoms of the snakes Daboia russelii, Echis carinatus, Hypnale hypnale, and Naja naja from Sri Lanka. The preclinical neutralizing ability of this antivenom against several toxic and enzymatic activities of these four venoms was analyzed, and compared with that of a batch of VINS antivenom (India) being currently used in Sri Lanka. The activities tested were: lethality, hemorrhagic, in vitro coagulant, proteinase and phospholipase A2 . Both antivenoms neutralized, to a different extent, these activities of the venom of D . russelii, E . carinatus, and N . naja . In general, the polyspecific Sri Lankan antivenom was more effective than the Indian antivenom in the neutralization of the venoms of D . russelii and E . carinatus, whereas the Indian antivenom showed a higher efficacy against the venom of N . naja . Regarding H . hypnale, the new Sri Lankan antivenom was effective in the neutralization of all activities tested, whereas the Indian antivenom neutralized lethality but not hemorrhagic, coagulant, proteinase and PLA2 activities, in agreement with the fact that this venom is not included in the immunization mixture for this antivenom. Results suggest that the new polyspecific Sri Lankan antivenom has a satisfactory preclinical neutralizing profile and compares favorably with the Indian antivenom. This is ready to be tested in a clinical trial to evaluate its efficacy and safety in human victims of snakebite envenomings by D . russelii, E . carinatus and H . hypnale in Sri Lanka. Graphical abstract: Highlights: A new polyspecific freeze-dried antivenom against venoms of Sri Lankan snakes was developed. Antivenom was raised against venoms of Daboia russelii, Echis carinatus, Hypnale hypnale and Naja naja . The new antivenom compares favorably with an Indian antivenom in the neutralization of these venoms. This is the first antivenom to include the venom of Hypnale hypnale in the immunizing mixture.